Study of the Antioxidant and Anti-Inflammatory Potential of the Aerial Parts of Ficus nitida L. (Moraceae) and its Phytochemical Composition - Rashed, khaled; Lai, Ching-Shu; Pan, Min-Hsiung; Feitosa, Chistiane (Jordan Journal of Pharmaceutical Sciences, 2018)
The aim of this investigation was to evaluate the antioxidant and anti-inflammatory activities of a methanolic extract of the aerial parts of Ficus nitida, and to investigate the main phytoconstituents present in the extract. The extract was tested for antioxidant activity by using 1,1-diphenyl-2-picrylhydrazyl (DPPH), and for anti-inflammatory potential by using a nitrite assay. The extract was also screened for phytochemicals by different chemical tests. The results showed that the Ficus nitida extract had significant antioxidant and anti-inflammatory effects that were concentration-dependent. Phytochemical analysis of the methanol extract proved the presence of alkaloids and/or nitrogenous compounds, carbohydrates and/or glycosides, flavonoids, tannins, and triterpenes and/or sterols. These results indicated that a methanolic extract of Ficus nitida aerial parts may act as a potential anti-inflammatory and antioxidant.